Sixty minutes of what? A developing brain perspective for activating children with an integrative exercise approach. Issue 23 (23rd January 2015) - Myer, Gregory D; Faigenbaum, Avery D; Edwards, Nicholas M; Clark, Joseph F; Best, Thomas M; Sallis, Robert E
Abstract : Current recommendations for physical activity in children overlook the critical importance of motor skill acquisition early in life. Instead, they focus on the quantitative aspects of physical activity (eg, accumulate 60 min of daily moderate to vigorous physical activity) and selected health-related components of physical fitness (eg, aerobic fitness, muscular strength, muscular endurance, flexibility and body composition). This focus on exercise quantity in youth may limit considerations of qualitative aspects of programme design which include (1) skill development, (2) socialisation and (3) enjoyment of exercise. The timing of brain development and associated neuroplasticity for motor skill learning makes the preadolescence period a critical time to develop and reinforce fundamental movement skills in boys and girls. Children who do not participate regularly in structured motor skill-enriched activities during physical education classes or diverse youth sports programmes may never reach their genetic potential for motor skill control which underlies sustainable physical fitness later in life. The goals of this review are twofold: (1) challenge current dogma that is currently focused on the quantitative rather than qualitative aspects of physical activity recommendations for youth and (2) synthesise the latest evidence regarding the brain and motor control that will provide the foundation for integrative exercise programming that provide a framework sustainable activity for life.